Emerging Regenerative Approaches for Periodontal Reconstruction: Practical Applications From the AAP Regeneration Workshop. Issue 1 (1st February 2015) - Rios, Hector F.; Bashutski, Jill D.; McAllister, Bradley S.; Murakami, Shinya; Cobb, Charles M.; Patricia Chun, Yong‐Hee; Lin, Zhao; Mandelaris, George A.; Cochran, David L.
Abstract : Focused Clinical Question: Can emerging technologies for periodontal regeneration become clinical reality? Summary: Emerging technologies are presenting options to hopefully improve the outcomes of regeneration in challenging clinical scenarios. Cellular allografts represent a current technology in which cells and scaffolds are being delivered directly to the periodontal lesion. Recombinant human fibroblast growth factor 2 and teriparatide (parathyroid 1‐34) have each been tested in controlled prospective human randomized clinical trials, and both have been shown to have potential for periodontal regeneration. These examples, as well as other emerging technologies, show promise for continued advancement in the field of periodontal regenerative therapy. Conclusions: At present, there are indications that emerging technologies can be used successfully for periodontal regeneration. Case reports and clinical trials are being conducted with a variety of emerging technologies. However, many are yet to be approved by a regulatory agency, or there is a lack of evidence‐based literature to validate their expanded use.